Dolutegravir Plus Lamivudine Maintains Human Immunodeficiency Virus-1 Suppression Through Week 48 in a Pilot Randomized Trial. (21st December 2017) - Taiwo, Babafemi O; Marconi, Vincent C; Berzins, Baiba; Moser, Carlee B; Nyaku, Amesika N; Fichtenbaum, Carl J; Benson, Constance A; Wilkin, Timothy; Koletar, Susan L; Colasanti, Jonathan; Acosta, Edward P; Li, Jonathan Z; et al.
Abstract: In this randomized pilot clinical trial, dolutegravir plus lamivudine was noninferior to continuation of standard 3-drug maintenance antiretroviral therapy. There was no emergence of drug resistance in the participant who experienced virologic failure while receiving dolutegravir plus lamivudine. Clinical Trials Registration: NCT02263326